Analysis on influencing factors of hemodialysis adequacy in maintenance hemodialysis patients - GAO Yan; FANG Yan-hui; GAO Tong-xin; GUO Xue-na; REN Jian-wei (Linchuang shenzangbing zazhi)
Objective To explore the influencing factors of adequacy of single hemodialysis in maintenance hemodialysis(MHD) patients.Methods A total of 109 patients who underwent MHD in Blood Purification Centre of Aviation General Hospital in March 2019 were enrolled in this study.The data on pre-HD and post-HD gender,age,body mass index(BMI),primary disease,vascular access and blood urea nitrogen(BUN),hemodialysis time,ultrafiltration volume(UF),blood flow rate(BFR),dry body weight and ratio of UF in single hemodialysis were recorded.According to spKt/v results,the patients were divided into two groups:qualification group(spKt/V≥1.2) and disqualification group(spKt/v<1.2).The influencing factors were analyzed.Results Univariate analysis showed that spKt/V was correlated with gender,dialysis associated coagulation,BFR,arteriovenous fistula(AVF)and dry body weight(P<0.05).Binary Logistic regression showed that gender(OR=4.345,95%CI 1.240～15.070,P<0.05),dialysis associated coagulation(OR=5.497,95%CI 1.213～27.125,P<0.05),BFR(OR=0.984,95%CI 0.969～0.998,P<0.05) and AVF as vascular access(OR=0.105,95%CI 0.012～0.889,P<0.05) were independent influencing factors of spKt/V for single hemodialysis.Conclusions The single hemodialysis adequacy in MHD patients is closely associated to gender,dialysis associated coagulation,BFR and AVF.